Relations Between the USSR and the Vatican and Soviet Policy Towards the Church in Lithuania between 1945–1978 - Streikus, Arūnas (Genocidas ir rezistencija, 1999)
Soviet policy towards the Catholic Church in Lithuania depended on the character of relations between Moscow and the Vatican. The hostility between Moscow and the Vatican added to an already extremely difficult situation for the Catholic Church during the last decade of Stalin’s reign. Those tense relations led to attempts to reorganise the Catholic Church in Lithuania into an independent national church. After Stalin’s death the Soviets changed the tacties of their foreign policy and the policy towards the Church. Consequently the relations between Moscow and the Vatican took new shape. The Soviets abandoned the discriminatory policy towards the Catholic Church and gave consent to Lithuania to re-establish linkages with the Vatican, of course, controlled by the Soviets. Both, the Soviets and Lithuania, benefited by the détente. On one hand, the Soviets with no disguise could consolidate the status and authority of the Catholic clergy loyal to the regime. On the other hand, the communication of the Church of Lithuania with the outside world greatly contributed to a successful end of suppression and gradual establishment of rights for the faithful.
Keywords: Soviet Union; Vatican; Soviet religiuos policy; Catholic church